Estudo de conversores bidirecionais trifásicos para aplicação em estações de recarga de baterias de veículos elétricos - Reis, Francisco Everton Uchôa (2020)
This thesis consists of the study of two bidirectional current converters capable of controlling the power flow between ac power grid to the dc link of a possible electric vehicle battery charging station (EVs). Thus, it is important that the chosen topologies have the ability to operate either as ac-dc or dc-ac converters. The main goal is to determine which structure is best suitable for this type of application considering the power levels required by charging stations of electric vehicles (EVs). In this context, this work shows the study of a three-phase, three-level stack neutral point clamped (3L-SNPC) bidirectional converter, which is derived from a neutral point clamped (NPC) converter, for applications in EV charging stations. The 3L-SNPC converter has a better uniform distribution of losses among the semiconductors and higher degree of freedom regarding the operation of active switches. The classic NPC converter is also studied for the same application and for comparison with the 3L-SNPC topology. The analyzed converters are capable of operating in either ac-dc or dc-ac mode with high power factor, also employing the same control and modulation strategy. The main advantages include the existence of a three-level voltage waveform across each arm and the neutral, the voltages across all semiconductors are equal to half the total dc-link voltage, and the voltages across the dc-link capacitors are balanced as imposed by a control action. The design of current and voltage control loops is properly presented to ensure high power factor, low harmonic distortion of the current, and regulation of the dc output voltage. In order to validate the study, simulation results are presented for the two aforementioned structures for a rated power of 2 kW. Simulation results for the three-phase version at a total power of 6 kW are also discussed in detail. Finally, experimental results are presented for the 3L-SNPC converter in terms of a single-phase version to validate the whole theoretical analysis.